FITTING OF TONAL CURVE AND BALANCING OF GRAY LEVELS IN CONTRAST EXPANSION AND PRELIMINARY IMAGING OF STRUCTURES IN THE ANALYSIS - Ogiela, Marek R. (Computer Science, 2020)
The article presents a group of transformations which medical pictures can be subjected to, in the aim of enhancing their contrast and better distinguishing and diagnosis of organs shown in this pictures. In this work the analysis was based on images acąuired by various techniąues, such as roentgenography (RTG), magnetic resonance (MRI), classic Computer tomography (CT) and ultrasonography (USG). Contrast expansion in these images was performed using the histogram mcthod of balancing of gray levels and the method based on the modification of tonal curve. Such transformations were necessary during preliminary processing of these images, especially to adjust their quality for next steps of the analysis in case of automatic medical diagnosis, and also to enable their visua! evaluation by specialists and diagnostic interpretation of images of or gans and their structural features. The studies show that the method based on the modification of tonal curve yields better results in case of images acąuired by roentgenography and magnetic re sonance imaging. On the other hand, histogram method is morę suitable for contrast expansion in CT and USG images.